Evaluation of biological measures and multipurpose adaptive grass on soil bund in Lasta district, Ethiopia - Haymanot Lamesgn Zena; Yalelet Abie (Heliyon, 2023)
The adverse effect of soil erosion is a major problem in Ethiopia, and soil and water conservation efforts must do to reduce the impact. Use of biological measures (grasses) combined with soil bund have numerous impact for reducing soil nutrient loss and increase soil moisture conservation, secure animal fodder for farm owners in low grass potential areas, enhance productivity of land and green biomass, but its adoption has been limited in the study area. This study explored the effect of grasses combined with soil bund on the experiment want to see the effect of stabilizer grasses on soil bund have seven treatments with randomized complete block design. Moisture content and bulk density data were collected and analyzed, taken undisturbed soil sample by gravimetric method, survival rate available plant per total planted times 100, tiller total number, plant height via meter and biomass using hanging balance data's were collected. The data analysis was done using R-Software and for mean separation, LSD at 5% significance level was used for moisture, bulk density, survival rate, biological parameters. Grass have positive impact on moisture content and bulk density to increase ease of use of water for grass and to stabilize the bund results in 2020 was 22.2%, 17.56%, and 12.3% of difference vetiver, Sudan grass, elephant and panicum in 2021 13% (1.36) in Sudan grass with comparison of the control treatment (1.57), respectively. Sudan grass and panicum have (100%) and (80%) performance on survival rate to rehabilitate and support the bund and protect direct runoff. Panicum has scored 77.2 average tillers in 0.15 m2 area on number of tiller that can affect biomass and direct runoff. Sudan grass 98.7 cm, elephant 85.4 cm and panicum 81 cm was resulted in 2021 and in 2020 Sudan grass 136.4 cm, elephant 91 cm and panicum 78.3 cm record on plant height. The green biomass that have great contribution for forage and other multipurpose use was Sudan grass, elephant and panicum yielded 20.8 t/ha in 2020 12.7 t/ha and 10.6 t/ha in 2022 respectively. Overall, in the experiment Sudan grass, Panicum Coloratum and Elephant grass have better adaptability and survival, increase farm land productivity contributing additional grass proceeds and have multipurpose use of fodder production.